Anastomosing Hemangioma Incidentally Found in Kidney or Adrenal Gland: Study of 10 Cases and Review of Literature - Zhou, Jun; Yang, Xiaoqun; Zhou, Luting; Zhao, Ming; Wang, Chaofu (Urology Journal, 2020)
Purpose: To describe and report a series of renal and adrenal anastomosing hemangioma (AH) and to investigate its distinctive clinicopathologic features and review its clinical data available in the literature. Materials and Methods: Clinical data of 10 AHs were retrospectively studied. Imaging and histologic features were re-evaluated and summarized. Immunostaining markers were performed include CD31, CD34, ERG, Fil-1, D2-40, AE1/AE3, SMA, CD10, HHV8, S100, Ki-67. A follow-up of all cases was performed. Other AHs published in PubMed and Web of Science were reviewed. Results: All of 10 AHs were found incidentally, containing 5 female and 5 male patients (median, 48.5 years; mean, 51.7 years) and involved unilateral kidney (n=7) and adrenal glands (n=3) respectively. All lesions were well-defined in Imaging and histologic examination. AHs were morphologically characterized by prominent anastomosing vascular channels without evidence of infiltration to surrounding normal tissues and significant cellular atypia. CD31, CD34, ERG were positive and Ki-67 showed typically low (?3%). All Patients underwent a mass resection and none of them had evidence of recurrence. Together with other cases published, the AHs showed distinctive clinicopathologic features with an excellent prognosis. Conclusion: Renal or adrenal AH is a very rare vascular tumor. They have distinctive histologic features and a favorable prognosis. Its frequently mimicking well-differentiated angiosarcomas easily result in unnecessary overtreatment in clinical practice. To be acquainted with this entity serves to avoid misdiagnosis.